Diversity of Local Responses to Integrated Conservation and Development Projects (Sustainability in Debate, 2015)
Integrated Conservation and Development Projects, a biodiversity conservation strategy, hasbeen widely adopted by NGOs and international cooperation agencies in recent decades. Theseprojects are characterized by conservation objectives associated with the socioeconomic developmentof local populations living inside protected areas or in their neighborhoods. In this paper,the author analyzes 25 project evaluations in 18 countries, identifying the spectrum of triggeredresponses. From this base, 34 different responses were identified, which highlights the potentialof these projects to produce changes in local systems. However, in half of the cases (14 of 25),the actions developed by the projects produced no identifiable responses, and among the casesin which responses were effectively observed, many of them appeared to have the potentialfor counter-productive effects. Results point to the risks associated with these biodiversity conservationinterventions, and show the need to approach their design, evaluation and scientificresearch from a systemic point of view.